Changes in Subcellular Responses in the Digestive Gland of the Freshwater Mussel Unio crassus from a Historically Contaminated Environment - Zoran Kiralj; Zrinka Dragun; Jasna Lajtner; Krešimira Trgovčić; Tatjana Mijošek Pavin; Bruno Bušić; Dušica Ivanković (Fishes)
Utilizing a multi-biomarker approach, we assessed the potential adverse effects of pollutants on subcellular responses in the digestive gland of the freshwater mussel Unio crassus from a historically contaminated lowland section (KIZ) of the river Mrežnica compared to its less impacted upstream karstic section (REF) and their seasonality (spring vs. autumn). This approach accounted for the diverse modes of action of pollutants by including biomarkers of metal exposure (metallothioneins, MT), general stress (total cytosolic proteins, TP), antioxidative capacity (catalase, CAT; glutathione, GSH; glutathione-S-transferase, GST), oxidative damage (malondialdehyde, MDA), and neurotoxicity (acetylcholinesterase, AChE). Only in spring, MT concentrations were 15% higher at the REF site (4.38 ± 1.06 µg mg proteins−1) compared to the KIZ site (3.69 ± 0.63 µg mg proteins−1), likely related to elevated Cd bioaccumulation due to the karstic substrate. Regardless of the season, mussels from KIZ showed consistently lower TP and GSH, with significantly higher CAT, GST, and MDA levels, indicating elevated stress, activation of antioxidant defenses, and oxidative damage from chronic exposure to pro-oxidant pollutants, including metal(loid)s and organic contaminants (e.g., ibuprofen, nicotine). Compared to the REF site, AChE activity at the KIZ site was higher in late spring and lower in early autumn, indicating seasonal variability in AChE activity at the contamination-impacted location driven by fluctuating exposure to neurotoxicants, such as drugs and insecticides. Overall, biomarker responses indicated that mild historical pollution, reinforced by current low-capacity sources, has an observable impact on mussel health, posing long-term risks to sediment-dwelling aquatic organisms.